Pelatihan dan Pendampingan Pengolahan Air Bersih Bagi Masyarakat Kampung Yobeh Distrik Sentani Kabupaten Jayapura - Suhartawan, Bambang; Suyatno, Suyatno; B. Alfons, Alfred; Abel, Andrea K.M.; Sroyer, Katherina (LPPM Uncen, 2025)
Yobeh Village is part of the Sentani district and has 3 RWs and 7 RTs with 173 heads of families and a total population of 692 people. Some of the people of RW2 Kampung Yobeh live on the coast of the island in the Sentani lake area, approximately 56 families with a population of approximately 246 people. The waters of Lake Sentani are the